A novel N-terminal motif is responsible for the evolution of neural crest-specific gene-regulatory activity in vertebrate FoxD3 - Ono, Hiroki; Kozmik, Zbynek; Yu, Jr-Kai; Wada, Hiroshi (Developmental biology, 2014)
The neural crest is unique to vertebrates and has allowed the evolution of their complicated craniofacial structures. During vertebrate evolution, the acquisition of the neural crest must have been accompanied by the emergence of a new gene regulatory network (GRN). Here, to investigate the role of protein evolution in the emergence of the neural crest GRN, we examined the neural crest cell (NCC) differentiation-inducing activity of chordate FoxD genes. Amphioxus and vertebrate (Xenopus) FoxD proteins both exhibited transcriptional repressor activity in Gal4 transactivation assays and bound to similar DNA sequences in vitro. However, whereas vertebrate FoxD3 genes induced the differentiation of ectopic NCCs when overexpressed in chick neural tube, neither amphioxus FoxD nor any other vertebrate FoxD paralogs exhibited this activity. Experiments using chimeric proteins showed that the N-terminal portion of the vertebrate FoxD3 protein is critical to its NCC differentiation-inducing activity. Furthermore, replacement of the N-terminus of amphioxus FoxD with a 39-amino-acid segment from zebrafish FoxD3 conferred neural crest-inducing activity on amphioxus FoxD or zebrafish FoxD1. Therefore, fixation of this N-terminal amino acid sequence may have been crucial in the evolutionary recruitment of FoxD3 to the vertebrate neural crest GRN.
Keywords: crista neuralis; vývojová regulace genové exprese; FoxD3; represorové proteiny; forkhead transkripční faktory; Repressor Proteins; Transcription, Genetic; Neural Crest; Neural crest; Cloning, Molecular; genetická transkripce; Gene Expression Regulation, Developmental; obratlovci; Forkhead Transcription Factors; zvířata; Amphioxus; Vertebrates; klonování DNA; Animals